CRETACEOUS ACCRETIONARY COMPLEX RELATED TO OKHOTSK-CHUKOTKA SUBDUCTION, OMGON RANGE, WESTERN KAMCHATKA, RUSSIAN FAR EAST - Soloviev A.; Ledneva G.; Garver J.I. (My University, 2006)
The Omgon Range of Western Kamchatka contains a mid to Upper Cretaceous sequence of flysch with tectonic inclusions of Jurassic-Cretaceous oceanic rocks inferred to have been imbricated together in an accretionary prism. These rocks were tectonically juxtaposed during the Cretaceous in a mélange that contains a number of elements but mainly includes: (1) Middle Jurassic-Lower Cretaceous volcanic rocks formed in an oceanic and/or marginal sea environment; and (2) Albian-Campanian terrigenous turbidites made of quartz-rich clastic sediments that accumulated near a continental-margin. The oceanic rocks are inferred to have been tectonically incorporated into the continental terrigenous unit by offscraping during subduction. The accretionary prism resulted from subduction of the Pacific paleo-oceanic plate (Izanagi) under the Eurasian continental margin, which ultimately caused volcanism in the inboard Okhotsk-Chukotka volcanic belt. Internal imbrication was completed by the Maastrichtian (~70 Ma) as indicated by apatite fission-track ages that record cooling and exhumation of this crustal block. The Omgon accretionary wedge originated in a similar geodynamic setting and same time as the Yanranai (northern Korayk), Tonino-Aniva (southeastern Sakhalin), Hidaka (northeastern Japan) and Cretaceous part of the Shimanto belt (southwestern Japan). The similarities of ages, lithology, and tectonic setting suggest that the Omgon accretionary wedge was part of a paleo-subduction zone along the Eurasian margin during the mid to Late Cretaceous. © 2005 Elsevier Ltd. All rights reserved.
Keywords: ACCRETIONARY WEDGE; FISSION-TRACK; KAMCHATKA; MÉLANGE, CRETACEOUS; Jurassic; Maastrichtian; Campanian; Albian; Mesozoic::Jurassic; Мезозой::Юрская; Mesozoic::Cretaceous::Upper::Maastrichtian; Мезозой::Меловая::Верхний::Маастрихтский; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский